2002
DOI: 10.1093/jjco/hyf098
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose Weekly Paclitaxel as Second-line Treatment for Advanced Non-small Cell Lung Cancer: a Phase II Study

Abstract: A low-dose weekly paclitaxel regimen had good clinical efficacy with low toxicity in this group of patients with poor prognosis. This regimen increases the therapeutic options available for second-line therapy in NSCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Response rates with paclitaxel of the range of 0 -38% in previously published studies (Socinski et al, 1999(Socinski et al, , 2002Juan et al, 2002;Sculier et al, 2002a;Buccheri and Ferrigno, 2004;Ceresoli et al, 2004;Yasuda et al, 2004), and of the order of 7.7 and 11.6% in PF and SF patients, respectively, observed in the present study are similar to those with docetaxel, ranging from 2.7 to 12.6% (Fossella et al, 2000;Shepherd et al, 2000;Gridelli et al, 2004;Hanna et al, 2004;Quoix et al, 2004;Gervais et al, 2005;Schuette et al, 2005;Camps et al, 2006).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Response rates with paclitaxel of the range of 0 -38% in previously published studies (Socinski et al, 1999(Socinski et al, , 2002Juan et al, 2002;Sculier et al, 2002a;Buccheri and Ferrigno, 2004;Ceresoli et al, 2004;Yasuda et al, 2004), and of the order of 7.7 and 11.6% in PF and SF patients, respectively, observed in the present study are similar to those with docetaxel, ranging from 2.7 to 12.6% (Fossella et al, 2000;Shepherd et al, 2000;Gridelli et al, 2004;Hanna et al, 2004;Quoix et al, 2004;Gervais et al, 2005;Schuette et al, 2005;Camps et al, 2006).…”
Section: Discussionsupporting
confidence: 87%
“…Similar were MST with paclitaxel in previous studies, ranging from 4.5 to 14 months (Socinski et al, 1999(Socinski et al, , 2002Juan et al, 2002;Sculier et al, 2002a;Buccheri and Ferrigno, 2004;Ceresoli et al, 2004;Yasuda et al, 2004). The equivalence of both drugs was evaluated in one small randomised phase II study only.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Relatively low dose of Tx (10 nM) was used for the understanding of the study because it has been reported that low dose of Tx can show tumour control with lesser toxicity to normal cells. 23,24 Moreover, due to poor vascularisation, various portions of cancer tissue are known to develop resistance phenomenon for low exposure to drugs; therefore, low drug dose is physiologically more significant than higher doses. At early stage, cancer cells showed sensitivity to exposure with low dose Tx (10 nM) and thereafter those gradually became resistant to it over a period of 40 days.…”
Section: Introductionmentioning
confidence: 99%
“…Phase II studies [126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142] and a follow-up study of all the patients who received paclitaxel as second-line chemotherapy after a randomised phase III trial [143] have demonstrated the activity of the single agent paclitaxel. The equivalent of docetaxel and pemetrexed was evaluated in one small randomised phase II study which found no statistically significant difference in terms of response rate (14 versus 3%) and median survival (105 versus 184 days) [144].…”
Section: Which Are the Recommended Second-line Regimens?mentioning
confidence: 99%